FIQH SAINS: ELABORASI KONSEP ‘ILLAT MENUJU PEMBENTUKAN HUKUM ISLAM YANG AKTUAL - Sodiqin, Ali (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
Fiqh is the nearest part in the religious life of the Islamic society. Almost all of the religious practices in the society are besed on the fiqh. On the other hand, fiqh is the product of fuqaha’s ijtihad which open to the change and diversity. The one of causes which became the change and diversity in fiqh is illat concept. The existing or lacking of law are dipend on the illat, therefor the illat of law elaboration became very important. The science and tecnology development can be recognized as the illat of law change. The law which had been formed by the classic and medieval ulama can be canged. It is not effective in the science and tecnology development era. The finding of new law become the new law illat. The concepts of majlis, safar, iddah need to be interpreted because of theinformation and transportation tecnology development. Therefore, it is impoetant to develope the concept of illat which is suitable with the Islamic law formative orientation (maqasid asy-syari’ah). The illat of law must capable to make law which is implied the mashlahah and relevant to the civilization development, in order to keep the fiqh flexibility and significancy to the life realities. The process can be conducted by activizing ijtihad, fusing between the istinbat (deductive) and istiqra’ (induktif) methods. The ijtihad model depends on the real problems, einther by using the tarjih intiqa‟i or ibdai insyai models.